Study of Traditional Uses of Medicinal Plants (Herbs) of Hilly Areas of Lekhnath Municipality - Dwa, Om Prasad (Janapriya Journal of Interdisciplinary Studies, 2017)
The present work is based on the exploration of traditional use medicinal plants ethonobotanically, of Lekhnath Municipliaty, Kaski. A general survey and study of medicinal plants, particularly wild and cultivated herbs was conducted from 1st Oct. 2012 to 30th Apr. 2013. This paper deals about 24 species of medicinal herbs belong to 21 families. Included families are Amaranthaceae, Asteraceae (4), Cannabinaceae, Caryophyllaceae, Chenopodiaceae, Commelinaceae, Crassulaceae, Cyperaceae, Dioscoreaceae, Euphorbiaceae, Labiatae, Leguminosae, liliaceae, Malvaceae, Nyctaginaceae, Oxalidaceae, Primulaceae, Scrophulariaceae, Trapaceae, Urticaceae and Zingiberaceae. This result was based on survey carried out consulting participatory techniques to collect detailed information about collection and utilization of traditional medicinal plants at that area. Important information and other details about the respective plants were collected by discussion with native inhaler, traditional medicine practitioners and villagers. Showing them the sample of the plants. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 82-89